2017
DOI: 10.1111/iej.12881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apical transportation and centring ability of five thermally treated NiTi rotary systems

Abstract: All the thermally treated systems resulted in similar apical transportation. In the cervical region, the Hyflex CM and Prodesign Logic systems were associated with more centred preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 28 publications
(84 reference statements)
5
70
0
7
Order By: Relevance
“…The flexibility of Hyflex EDM was found to be similar to other CM Wire instruments (Goo et al 2017, Iacono et al 2017. Hyflex EDM has been reported to create a centred root canal preparation, respecting the original root canal anatomy ( € Ozy€ urek et al 2017, Pinheiro et al 2018, Venino et al 2017). In addition, Hyflex EDM instruments revealed a greater angle of rotation at fracture but a lower torque to fracture than M-Wire instruments (Pedull a et al 2016).…”
Section: Electrical Discharge Machining (Hyflex Edm)mentioning
confidence: 65%
“…The flexibility of Hyflex EDM was found to be similar to other CM Wire instruments (Goo et al 2017, Iacono et al 2017. Hyflex EDM has been reported to create a centred root canal preparation, respecting the original root canal anatomy ( € Ozy€ urek et al 2017, Pinheiro et al 2018, Venino et al 2017). In addition, Hyflex EDM instruments revealed a greater angle of rotation at fracture but a lower torque to fracture than M-Wire instruments (Pedull a et al 2016).…”
Section: Electrical Discharge Machining (Hyflex Edm)mentioning
confidence: 65%
“…, Pinheiro et al . ). In addition, even after the use of larger instruments, the transportation of all groups did not exceed 0.15 mm, which is considered an acceptable value indicating a satisfactory maintenance of the canal trajectory (Peters , Pinheiro et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, even after the use of larger instruments, the transportation of all groups did not exceed 0.15 mm, which is considered an acceptable value indicating a satisfactory maintenance of the canal trajectory (Peters , Pinheiro et al . ). These results are in line with those of other studies that showed that RB and WOG had similar shaping ability (Bürklein et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations